Optimised function for determining time to peak creatine kinase and creatine kinase-MB as non-invasive reperfusion indicators after thrombolytic therapy in acute myocardial infarction - Schwerdt, Holger; Özbek, Cem; Fröhlig, Gerd; Schieffer, Hermann; Bette, Ludwig (Cardiovascular research, 1990)
Study objective – The aim of the study was to investigate the use of an optimised function to approximate and interpolate the time course of serum creatine kinase and creatine kinase-MB values after thrombolytic therapy in acute myocardial infarction. Design – A three parameter interpolating function was developed which approximates the time course of serum enzyme levels. In the proposed function, time to peak creatine kinase and maximum of creatine kinase determined from raw data were used as starting parameters of the non-linear interpolation routine, thus providing ideal starting conditions for the iteration. The efficacy of the function was compared with that of three other functions cited in published reports (log-normal distribution function, modified gamma density function, three compartment function). Subjects – Serum enzyme data from 20 patients with acute myocardial infarction were used in the comparisons. The patients have all been treated with anisoylated plasminogen streptokinase activator complex. Results – In comparison with the other models, deviations of the experimental model function from the raw data were minimal. The fit remained stable for time intervals between blood samples of up to 6 h. Conclusions – Due to its numerical stability, the function outlined in this study is suitable for large clinical reperfusion trials. In the case of uncomplicated infarctions without thrombolytic therapy, the area under the creatine kinase activity curve could be directly calculated in terms of maximum activity and time to peak.